EXPERIMENTS ON INDUCED SPAWNING OF INDIAN CARPS WITH PITUITARY INJECTIONS - Chaudhury, Hiralal (Indian Journal of Fisheries, 2015)
One of the main problems confronting the progress of pisciculture in India is the dearth of fish seed of cultivated species of fishes for stocking ponds, tanks and reservoirs all over the country. The Indian carps, which are the main cultivated fishes, do not normally breed in confined waters although they attain maturity in such waters. They breed in riverine habitats and it is an age-old practice amongst fishermen to collect, from the rivers in North-Eastern part of India in specially designed nets, fertilised eggs and newly hatched larvae (spawn) which drift along in river margins. The spawn thus collected is usually a mixture of economic and uneconomic species of fishes. Often the percentage of economic variety is low. As at present there is no means of sorting the different varieties at this stage the fish farmer has to take a chance and is quite often disappointed with the result. Besides this method involves eff"ort of collection, transport, mortality during transport, high cost involved and above all uncertainty of availability of spawn or fry at the required time.